Technical specifications for the procurement of power transformers - Ristić, Mihajlo; Maksimović, Slobodan; Pejović, Branko; Jovanovic, Djordje; Teslić, Dragan; Radojčić, Miroslav; Radin, Vesna (Proceedings, Electrical engineering institute "Nikola Tesla", 2025)
The paper presents a comprehensive and complex project of the Internal Standard, IS2 Technical specifications for the procurement of power transformers, for the needs of Elektroprivreda Srbije ad (EPS ad), according to contract no. 2.5.0.012.01 - 39646/4-2022 and 02/04/5076-22 dated 29.12.2022. The project deals with 21 chapters, according to the program task and includes 209 pages. Considering the complexity of the project, it also contains 6 shemas and 25 table views. The project was adopted by the Expert Council of EPS ad.